2022
DOI: 10.1128/spectrum.02560-21
|View full text |Cite
|
Sign up to set email alerts
|

Convalescent Plasma for Preventing Critical Illness in COVID-19: a Phase 2 Trial and Immune Profile

Abstract: Transfusion of high-titer CIP to non-critically ill patients early after admission with COVID-19 respiratory disease was associated with significantly increased anti-SARS-CoV-2 specific antibodies (compared to baseline) and a non-significant reduction in ICU transfer and death (compared to controls). This prospective phase II trial provides a suggestion that the antiviral effects of CIP from early in the COVID-19 pandemic may delay progression to critical illness and death in specific patient populations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28-day mortality, and a double-blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival. Observational studies [46][47][48][49][50][51][52][53][54] have reported mixed findings, but generally suggest that efficacy is more likely with high titer CCP in earlier and less severe disease, [46][47][48][49][50][51][52][53] or when used in those with impaired immunity. [55][56][57] Interpretation of RCT data, including those in recent metaanalyses, 58,59 is made challenging for multiple reasons: 1) the use of either untitered plasma or plasma qualified by serologic testing alone,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28-day mortality, and a double-blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival. Observational studies [46][47][48][49][50][51][52][53][54] have reported mixed findings, but generally suggest that efficacy is more likely with high titer CCP in earlier and less severe disease, [46][47][48][49][50][51][52][53] or when used in those with impaired immunity. [55][56][57] Interpretation of RCT data, including those in recent metaanalyses, 58,59 is made challenging for multiple reasons: 1) the use of either untitered plasma or plasma qualified by serologic testing alone,…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the PennCCP2 trial (US) 44 found a benefit in the primary clinical endpoint of disease severity and 28‐day mortality, and a double‐blind RCT study by O'Donnell et al, (US and Brazil) 45 found CCP was not associated with significant improvement in day 28 clinical status, but was associated with significantly improved survival. Observational studies 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 have reported mixed findings, but generally suggest that efficacy is more likely with high titer CCP in earlier and less severe disease, 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 or when used in those with impaired immunity. 55 , 56 , 57 …”
Section: Discussionmentioning
confidence: 99%
“…Previously, there were studies suggesting the association between receiving CCP and lower 28-day mortality or less progression of diseases ( 67 70 ), while recent prospective studies and RCTs indicated that CCP could not lead to elevated antibody titer ( 71 ) or survival benefits in COVID-19 patients ( 72 , 73 ). Our findings supported that COVID-19 patients might not benefit from the transfusion of CCP, which was consistent with the latest WHO and IDSA guideline ( 53 , 54 ).…”
Section: Discussionmentioning
confidence: 99%